Molecular Characteristics of Blood Serum After Covid-19 Vaccination in a Remote Period - Pedachenko, Y.E.; Vasilieva, I.G.; Chopik, N.G.; Tsiubko, O.I.; Oleksenko, N.P.; Dmytrenko, A.B.; Makarova, T.A.; Shuba, I.M.; Педаченко, Є.Г.; Васильєва, І.Г.; Чопик, Н.Г.; Цюбко, О.І.; et al. (PH "Akademperiodyka" of the NAS of Ukraine, 2024)
COVID-19 is a dangerous disease with long-lasting consequences. Vaccination contributes to the accumulation of neutralizing anti-S IgG antibodies, reducing the incidence of COVID-19 and its complications. However, in some individuals, the inflammatory process can persist for an indefinite period and lead to a wide range of dysfunctions. The current task is to investigate molecular markers for their detection. The aim of this study is to examine the levels of anti-S IgG antibodies, lactate, glucose, lactate dehydrogenase, and C-reactive protein in the peripheral blood of individuals who have and have not been affected by COVID-19 after vaccination. The research subject is venous blood. Among 547 employees of the Neurosurgery Institute (481 vaccinated against COVID-19 and 66 unvaccinated individuals), levels of anti-S IgG antibodies were investigated, as well as levels of lactate, lactate dehydrogenase, glucose, and C-reactive protein. At the time of the study, among 372 individuals, 16 months had passed from the first vaccination, and 12 months had passed from the second vaccination; in 21 individuals, 12 months had passed after a single vaccination, and in 88 individuals, 16 months had passed from the first vaccination, 12 months from the second, and 6 months from the third vaccination. Methods. Quantitative determination of IgG antibodies to the S protein of the SARS-CoV-2 virus. Confirmation of COVID-19 using the RT-PCR method (Allplex 2019-nCoV kit, SeeGene, Korea). Levels of lactate, lactate dehydrogenase, glucose, and C-reactive protein were determined using reagents from BioSystems (Spain). Statistical analysis of the obtained data was performed using Jamovi software (USA) and the following criteria: χ2 ‒ Kruskal-Wallis, W ‒ Dwass-Steel-Critchlow-Fligner (DSCF), χ2 ‒ Pearson, t ‒ Student, rs ‒ Spearman, τb ‒ Kendall. A statistically significant difference was considered at p < 0.05. Results. The level of anti-S IgG antibodies to the SARS-CoV-2 virus was higher in vaccinated individuals compared to unvaccinated individuals (Kruskal-Wallis χ2=14.09; p < 0.001). A higher level of antibodies to the S protein of the virus was observed when using the Comirnaty vaccine compared to vaccination with Moderna, AstraZeneca, Pfizer, and CoronaVac (Dwass-Steel-Critchlow-Fligner (DSCF): W 4.26, p=0.002; W 4.62, p=0.010; W 4.84, p=0.006, respectively). Vaccination reduces the likelihood of contracting the disease by 1.84 times (Odds Ratio (OR) 1.84; 95% Confidence Interval (CI) 1.02‒3.30; χ2=4.129; p=0.043). However, no statistically significant dependence on the prevention of COVID-19 incidence based on the type of vaccines used was found (Kruskal-Wallis χ2=2.072; p=0.72). A statistically significant difference in C-reactive protein levels is observed between groups with early mild complications and early moderate-severity complications (DSCF: W=4.193, p=0.009). A statistically significant difference in LDH levels is noted between individuals without chronic diseases and those with chronic diseases at the time of the study (Kruskal-Wallis χ2=6.08, p=0.014). In individuals vaccinated against the SARS-CoV-2 virus, a positive correlation is found between the levels of C-reactive protein and lactate dehydrogenase (Kendall's τb 0.134, p < 0.001). The mean levels of lactate among individuals with mild, moderate, and severe forms of COVID-19 are higher than the reference mean; similarly, the mean levels of glucose in these same groups are higher than the reference mean. A positive correlation exists between the levels of lactate and glucose among individuals vaccinated against the SARS-CoV-2 virus (Kendall's τb 0.082, p < 0.01). Conclusions. Vaccination contributes to an increase in antibody levels. The level of antibodies after the third vaccination exceeded the levels after the first (Dwass-Steel-Critchlow-Fligner (DSCF): W 4.42, p=0.005) and second vaccinations (W 4.24, p=0.008). Vaccination reduces the likelihood of COVID-19 infection by 1.84 times (Odds Ratio ‒ 1.84; 95% Confidence Interval 1.02‒3.30; Pearson χ2=4.129; p=0.043). The frequency of COVID-19 incidence is not dependent on the type of vaccine used: AstraZeneca, Comirnaty, CoronaVac, Moderna, Pfizer (Kruskal-Wallis χ2=2.072; p=0.723), and the level of antibodies in the vaccinated individuals' serum. In the post-COVID-19 remote period, regardless of vaccination status, various complications are observed. However, among the vaccinated, the number of individuals without complications or with minimal complications is greater than in the unvaccinated group, while the number of individuals with early and severe complications is lower (Kruskal-Wallis χ2=6.127; p=0.047). A high level of C-reactive protein (DSCF: W=4.19, p=0.009), a tendency toward increased levels of lactate dehydrogenase (DSCF: W=3.27, p=0.054), elevated levels of lactate (2.17+1.23, t=3.34; p=0.002), and glucose (6.06+0.048, t=10.54; p < 0.001) indicate that after recovering from COVID-19, regardless the type of vaccines used,  in individuals with distant symptoms there are metabolic changes that are signs of a chronic inflammatory process. Individuals with chronic diseasees show an increase in the level of lactate dehydrogenase (χ2=6.08; p=0.014) and a tendency toward increased levels of C-reactive protein (χ2=3.74; p=0.053). Molecular markers of inflammation such as increased levels of lactate, glucose, C-reactive protein, and lactate dehydrogenase are informative for identifying individuals with an inflammatory process in the post-COVID-19 remote period.